2020
DOI: 10.1109/access.2020.2989132
|View full text |Cite
|
Sign up to set email alerts
|

A Nonparametric Repetitive Sampling DEWMA Control Chart Based on Linear Prediction

Abstract: Distribution-free control charts can be useful in statistical process control (SPC) when only limited or no information about the distribution of the data of the process is available. In this paper, a linear prediction related double exponentially weighted moving average (DEWMA) sign control chart using a repetitive sampling scheme (RSNPDEBLP) has been considered for a binomially distributed process variable to improve the efficiency of detecting small drifts in its place of small changes. The proposed RSNPDEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Note that parameter k simply expresses how many times the standard deviation of the monitoring statistic wriggles into the decision interval of the resulting chart. Shafqat et al (2020) introduced a linear prediction related double EWMA sign control scheme utilizing the repetitive sampling plan. The resulting control scheme is suitable for monitoring binomially distributed data and seems to be efficient in tracking down plausible small changes of the underlying process.…”
Section: A Nonparametric Double Ewma Sign Control Chartmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that parameter k simply expresses how many times the standard deviation of the monitoring statistic wriggles into the decision interval of the resulting chart. Shafqat et al (2020) introduced a linear prediction related double EWMA sign control scheme utilizing the repetitive sampling plan. The resulting control scheme is suitable for monitoring binomially distributed data and seems to be efficient in tracking down plausible small changes of the underlying process.…”
Section: A Nonparametric Double Ewma Sign Control Chartmentioning
confidence: 99%
“…Following a similar argumentation as the one provided by Brown and Meyer (1961), Shafqat et al (2020) constructed a double EWMA control chart for delivering linear predictions of the form…”
Section: A Distribution-free Repetitive Sampling Dewma Scheme Based On Linear Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the performance of the EWMA‐type control charts during start‐up period has never been addressed for the nonparametric SPM context. For some recent contributions to nonparametric charts, refer, for instance, to Mukherjee et al., 13 Triantafyllou, 14 Chong et al., 15,16 and Shafqat et al 17 . Next though, a literature review of some related parametric research works is discussed and thereafter, the objective of this paper is outlined.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the efficiency of the proposed control chart was better than that of the EWMA and TCC at all change levels. Besides, many authors developed and designed nonparametric control chart in several situations including, for instance, Abbas et al [19], Riaz et al [20], Shafqat et al [21], Chakraborti and Graham [22], and Mabude et al [23].…”
Section: Introductionmentioning
confidence: 99%